THE EFFECT OF USEFULNESS, EASE OF USE, AND ENJOYMENT TOWARDS ATTITUDE AND INTENTION TO USE E-READER: STUDY ON JAKARTA STATE UNIVERSITY’S STUDENTS - Rahmi, Rahmi (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2016)
The purpose of this research is to understand the effect of usefulness, ease of use, and enjoyment towards attitude and intention to use electronic book reader (e-reader). The conceptual model refers to Technology Acceptance Model theory. The research uses single cross-sectional descriptive research design to test the relationship among variables. Data is gathered with self-administered questionnaire survey method with Jakarta State University;s students as respondents. Hypotheses are tested with Structural Equation Model (SEM). The result shows that attitude still holds important role in forming intention, enjoyment comes as the strongest determinant for attitude and intention which emphasizes the hedonic value of e-reader, usefulness indirectly affects intention through attitude, and ease of use only affects usefulness and enjoyment but not attitude. Keywords: perceived usefulness, perceived ease of use, perceived enjoyment, attitude, intention.